2007
DOI: 10.1111/j.1551-2916.2007.01708.x
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Between Titanium and Zirconia Powders During Sintering at 1500°C

Abstract: Zirconia–titanium (ZrO2–Ti) composites have been considered potential thermal barrier graded materials for applications in the aerospace industry. Powder mixtures of Ti and 3 mol% Y2O3 partially stabilized ZrO2 in various ratios were sintered at 1500°C for 1 h in argon. The microstructures of the as‐sintered composites were characterized by X‐ray diffraction and transmission electron microscopy/energy‐dispersive spectroscopy. Ti reacted with and was mutually soluble in ZrO2, resulting in the formation of α‐Ti(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…Under the same sintering conditions, the volume fraction of m‐ZrO 2 increases with the increase of Ti content . In high‐temperature sintering at 1500°C, studies with 90 mol % Ti showed that ZrO 2 particles were almost completely dissolved in Ti, being accompanied by simultaneous precipitation of Y 2 Ti 2 O 7 …”
Section: Fabrication Techniques and Mechanical Behavior For Functionamentioning
confidence: 99%
“…Under the same sintering conditions, the volume fraction of m‐ZrO 2 increases with the increase of Ti content . In high‐temperature sintering at 1500°C, studies with 90 mol % Ti showed that ZrO 2 particles were almost completely dissolved in Ti, being accompanied by simultaneous precipitation of Y 2 Ti 2 O 7 …”
Section: Fabrication Techniques and Mechanical Behavior For Functionamentioning
confidence: 99%
“…where: d 2 -wall thickness of cake after casting time t 2 [mm], d 1 -wall thickness of cake after casting time t 1 [mm], f -correction factor for the viscosity of the water depending on the temperature, (slurry temperature at 21°C).…”
Section: Methodsmentioning
confidence: 99%
“…Ceramic-metal composites with a ceramic matrix can be shaped for bulk materials by method such as die pressing [1] or methods based on colloidal processing such as slip casting [2][3][4][5][6]. Slip casting is one of the most common methods used in ceramic technology.…”
Section: Introductionmentioning
confidence: 99%
“…ZrO2 has superior thermal and mechanical properties, which are effective for TBCs [19]. One of superior mechanical properties of ZrO2 is high fracture toughness due to stress-induced transformation (from tetragonal to monoclinic crystal structures under some stress conditions, which can be used in enhancement of fracture toughness of various ceramics and ceramic matrix composites [20][21][22].…”
Section: Open Accessmentioning
confidence: 99%